Participatory Integrated Climate Services for Agriculture (PICSA) as part of Rwanda Climate Services for Agriculture: Findings from quantitative evaluation of 2016/17 PICSA implementation - Clarkson, Graham; Dorward, Peter; Nsengiyumva, Gloriose; Kagabo, Desire (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The Rwanda Climate Services for Agriculture project aims to provide climate services across Rwanda. This report provides findings from the first year of implementation of the Participatory integrated Climate Services for Agriculture (PICSA) approach. A core team of national experts in PICSA were trained before cascading the approach to farmer groups through the Twigiri Muhinzi system of Farmer Promoters. Training of the first groups of Farmer Promoters took place in 2016. This document reports on a quantitative survey of 215 randomly selected trained farmers. The quantitative evaluation took place in March 2017 after the season had finished and respondents had been able to harvest. Results from the quantitative survey show that almost all of the farmers were trained on the PICSA elements that are implemented ‘long before the season’. 97% of respondents were trained in the seasonal forecast and 86% received short term forecasts during the season. 93% of farmers had made changes in their farming or other livelihood activities as a result of PICSA training. More farmers made changes in crops (90% of respondents) than livestock (24%) and other livelihoods (17%). On average respondents each made 2 changes. However, a larger proportion of men made changes in crops and livelihood enterprises than women. The most popular types of changes made in crops were growing a new crop (34%), growing a new variety of a crop they already grow (26%); and changing the management of land (23%). The most popular change in livestock enterprises were starting a new enterprise (14%), followed by increasing the scale of a livestock enterprise (6%); and changing the management of a livestock enterprise (4%). Regarding other livelihoods 9% of respondents had started a new enterprise and 7% had changed management of livelihood enterprises. Regarding the effects of the changes farmers had made as a result of the PICSA training, 85% of farmers reported that the decisions they had taken had improved their household food security. 81% reported that they had improved household income, 84% that they had been better able to provide for family healthcare and 75% that they had found it easier to pay their children’s school fees. Respondents reported that as a result of the PICSA training and the effects of the changes they had made that they are more confident in planning and decision making (96%), better able to cope with bad years caused by the weather (93%) and had improved their social standing within their households (93%) and within their wider community (93%). The results of this evaluation show that the first implementation of PICSA in Rwanda has been effective at scale across the first four districts. As the project scales the approach over the remaining districts in Rwanda it is vital to maintain quality in training and implementation. This success is due to PICSA being an integrated approach that enables farmers to assess their own individual farming systems and to evaluate and plan appropriate options in the context of their local climate and weather.